1995
DOI: 10.1111/j.1600-079x.1995.tb00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin counteracts lipid peroxidation induced by carbon tetrachloride but does not restore glucose‐6 phosphatase activity

Abstract: Carbon tetrachloride (CCl4) exerts its toxic effects by the generation of free radicals. In this study we investigated whether melatonin, a potent free radical scavenger, could prevent the deleterious effects of CCl4. Liver homogenates and liver microsomes were incubated with CCl4 in the presence of melatonin and lipid peroxidation and glucose-6 phosphatase (G6Pase) activity were determined. All doses of CCl4 (1, 0.5, 0.1 mM) produced significantly high levels of lipid peroxidation, as reflected by increased l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 27 publications
4
79
0
1
Order By: Relevance
“…Although a higher oxidative stress was postulated in SHR, SHR showed plasma malondialdehyde levels comparable to their WKY counterparts in our study. Other investigators have reported similar basal levels of malondialdehyde in SHR and WKY tissues [38], although increased lipid peroxidation in plasma and vascular intima was observed in SHR [39]. Some methodological and biological factors could explain these apparent contradictions in SHR.…”
Section: Discussionmentioning
confidence: 73%
“…Although a higher oxidative stress was postulated in SHR, SHR showed plasma malondialdehyde levels comparable to their WKY counterparts in our study. Other investigators have reported similar basal levels of malondialdehyde in SHR and WKY tissues [38], although increased lipid peroxidation in plasma and vascular intima was observed in SHR [39]. Some methodological and biological factors could explain these apparent contradictions in SHR.…”
Section: Discussionmentioning
confidence: 73%
“…[11][12][13][14][15][16][17] It has also been shown that when animals and tissues are subjected to lipid peroxidation, melatonin gives a substantial protection against the oxidative destruction of lipids. [18][19][20] The aim of this study was to examine the protective effects of melatonin against CCl 4 -induced hepatotoxicity in rats at biochemical and histological levels.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin is well known to scavenge oxygenfree radicals and to inhibit, in vitro and in vivo, lipid peroxidation generated by ethyl alcohol (36), carbon tetrachloride (37), and paraquat (38). This is the fi rst report that shows that melatonin also inhibits…”
Section: Resultsmentioning
confidence: 99%